Association between dietary behaviours and weight status of school children: results from the International Study of Childhood Obesity, Lifestyle and the Environment (ISCOLE) -Kenya. Issue Volume 4:Issue1(2021) (1st January 2021) - Wachira, Lucy-Joy; Muthuri, Stella; Ochola, Sophie; Onywera, Vincent; Tremblay, Mark
ABSTRACT: Background: Sub-Saharan African countries are undergoing rapid urbanization resulting in vast changes in dietary habits. Dietary practices involving excess energy intake have been associated with overweight/obesity. We assessed the dietary behaviour of children and their relationships with weight status. Methods: Data was collected in Kenya, as part of the International Study of Childhood Obesity, Lifestyle and the Environment (ISCOLE). The study recruited 563 children aged 9–11 years from 29 schools in Nairobi. A seven-day food frequency questionnaire was used to assess dietary intake. Dietary behaviours such as consumption of breakfast, school lunch, meals prepared/eaten away from home, emotional eating and snacking while watching television were also assessed. Body mass index (BMI-for-age and sex) was used as the indicator of weight status. Results: Of the sample, 53.5% were girls; 20.8% were classified as overweight/obese; 72.9% ate meals out of home regularly; 55.2% ate lunch provided by the school; and only 76% had breakfast on all weekdays. Eating more when happy, eating fried foods while watching television, and consumption of vegetables were positively associated with BMI. Majority of overweight children were female (56.6%) and the type of school attended predicted BMI, F(6, 536) = 18.371, p < 0.0001, R 2  = 0.171. BMI was negatively associated with consumption of cakes/pastries (χ 2  = 14.7, V = 0.165, p = 0.023), potato crisps (χ 2  = 21.6, V = 0.197, p = 0.003), and fast foods (χ 2  = 13.5, p = 0.036). ANOVA results revealed no significant differences in the consumption of foods with BMI except for vegetables (p = 0.003). Conclusions: Children have healthy diets rich in fruits and vegetables and low in energy-dense foods. Also, less healthy diets were observed in children with lower BMI. There is need for interventions targeting the overweight/obese children, particularly those of higher SES.